Fantasmagoriana Unfolded / Fantasmagoriana i utfoldelse - Francesco Ragazzi; Francesco Urbano (Nordnorsk kunstnersenter, 2022)
This text is the curatorial statement of the XVII edition of the Lofoten International Art Festival, the longest-running contemporary art Biennial in Scandinavia. It summarizes the themes approached and the methodology employed by the curators to organize the exhibition held at the North Norwegian Art Centre in Svolvaer and five sites in Kabelvåg, above the Arctic Circle, in 2022. The essay also describes the research background, residency programs, and preview projects in Venice and Oslo that preceded the inauguration of the biennial.